PENGARUH PEMBELAJARAN DARING TERHADAP KEMAMPUAN KOGNITIF SISWA - Dongoran, Jhonas; Septiani, Bronika (Jurnal Ilmiah Aquinas, 2022)
The spread of COVID-19 is the background in this study. As a result of the pandemic, it is necessary for the entire community to have social distancing, including the learning process which is carried out online or in a network. By applying online learning, it is necessary to conduct research on how it affects the cognitive abilities of students at SMP Padamu Negeri. This study aims to determine the effect of online learning on students' cognitive abilities on environmental pollution material for class VII SMP Padamu Negeri T.A 2020/2021. This research is a descriptive research using a quantitative approach. The population in this study were all students of class VII SMP Padamu Negeri totaling 50 students. Data collection techniques in this study used questionnaires, tests, and documentation. For data analysis techniques using quantitative descriptive analysis. From the results of the study, it can be concluded that online learning carried out in class VII-2 SMP Padamu Negeri on environmental pollution material for T.A 2020/2021 obtained an average value of 69.80. Meanwhile, students' cognitive abilities in the environmental pollution material in the 2020/2021 academic year have an average value of 50.35. Based on the results of a simple linear regression test, it was concluded that the coefficient of determination was 0.524 or equal to 40%, which means that online learning has an influence of 40% on students' cognitive abilities and the rest is influenced by other factors. The significance value obtained is 0.0001 which is smaller than the alpha of 0.05. Based on these data, it can be concluded that online learning has an effect on students' cognitive abilities. When Sig < 0.05 then Ha can be accepted while H0 is rejected. Where Ha is online learning has a significant effect on students' cognitive abilities and H0 is online learning has no effect on students' cognitive abilities.